Diseño racional, síntesis y evaluación biológica de heterociclos nitrogenados con actividad antiparasitaria - Casal, Juan José (2015)
Within the paradigm of rational drug design we developed a model of action with the aim of\ndesigning and synthesizing molecules that inhibit the trypanothione reductase, a specific enzyme\nfrom Trypanosoma cruzi which is essential for their survival in the host. Molecular docking techniques\nwere used to predict the ways in which substances could be attached to the protein, inhibiting its\naction, as well as relative strengths with which this union was done. These techniques have been\nused to establish three ways of drug development: the prediction of biological activity, the virtual\nscreening of commercial libraries of compounds and the design of new drug anti-trypanosomiasis.\nHowever, despite these chemical differences, substances synthesized and/or purchased have been\nshown to possess activity predicted by computers systems both in the assay with the enzyme, as\nwith in vitro assays with the parasite. We looked for alternative therapies through the synthesis of\nderivatives of phthalazine scaffold. Results showed a moderate biological activity, making these\ncompounds as leaders in the pursuit of the improvement of its pharmacological properties. We focus\non the development of nonsteroidal anti-inflammatory drugs (NSAIDs) for use as symptomatic cotreatment\nin Chagas? disease, which in its chronic stage presents inflammation and tissue damage.\nThe results were promising with two phthalimidic core leaders and a derivative of phthalazine with\nNSAID activity in vitro and in vivo.